Stepwise Improvement of Cerebral Hemodynamics in Staged Angioplasty for Carotid Artery Stenosis - Fumiaki OKA; Takayuki OKU; Akiko KAWANO; Koki OKAZAKI; Takuma NISHIMOTO; Mototsugu SHIMOKAWA; Hideyuki ISHIHARA (Neurologia Medico-Chirurgica)
Staged angioplasty (SAP) is used as an alternative to preventing cerebral hyperperfusion syndrome (CHS) after carotid artery stenting (CAS), particularly among patients with compromised cerebral haemodynamics. Although SAP is presumed to prevent CHS by gradually restoring cerebral blood flow (CBF), few studies have examined haemodynamic changes, and none have evaluated CBF during the chronic phase of SAP. In the present study, in addition to the clinical outcome of SAP, we measured both resting CBF and cerebrovascular reactivity (CVR) throughout all stages of SAP, including the chronic phase, using quantitative N-isopropyl-p-[I-123] iodoamphetamine (123I-IMP) single-photon emission computed tomography (SPECT) and evaluated the effects of SAP on cerebral haemodynamics. In total, 28 patients underwent SAP. Among them, 19 had a successful procedure. Nine received stenting at the first stage of the procedure because of inadequate dilatation. Patients who underwent SAP had a lower incidence of hyperperfusion than those who underwent stenting at the first stage (5.3% vs. 33.3%). Nevertheless, the results did not significantly differ (p = 0.08). In an analysis limited to the patients who underwent successful SAP, the resting CBF was unchanged except for immediately after the first stage, on the other hand, the CVR increased at each stage. After the first stage, 14 (74%) patients recovered from the steal phenomenon. After the second stage, the CVR normalised. SAP may help to improve cerebral haemodynamics gradually. Consequently, it has the potential to prevent CHS or hyperperfusion among patients with severely impaired CVR, which is a significant risk factor for CHS.